2013
DOI: 10.1016/j.jagp.2012.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Trial to Evaluate Potential Treatments for Apathy in Dementia: The Apathy in Dementia Methylphenidate Trial (ADMET)

Abstract: Background Research on efficacious treatments for apathy in Alzheimer’s disease has been hindered by a lack of consensus diagnosis, difficulties in measurement, and studies with small sample sizes. Methods In designing the Apathy in Dementia Methylphenidate Trial (ADMET), a trial to evaluate the efficacy and safety of methylphenidate for the treatment of apathy in Alzheimer’s disease, we encountered the following issues: defining and measuring apathy, distinguishing apathy and depression, determining an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…15 Participants were recruited at Johns Hopkins Bayview Medical Center (Baltimore, Maryland), Medical University of South Carolina (Charleston, South Carolina), and University of Toronto Sunnybrook Health Sciences Centre (Toronto, Ontario, Canada) between June 2010 and October 2011. Ethics review boards at all 3 institutions approved study procedures.…”
Section: Methodsmentioning
confidence: 99%
“…15 Participants were recruited at Johns Hopkins Bayview Medical Center (Baltimore, Maryland), Medical University of South Carolina (Charleston, South Carolina), and University of Toronto Sunnybrook Health Sciences Centre (Toronto, Ontario, Canada) between June 2010 and October 2011. Ethics review boards at all 3 institutions approved study procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, few controlled trials target treatment of apathy in AD. One recent randomized placebo-controlled trial of methylphenidate for apathy in AD (ADMET) reported improvement in two out of three efficacy outcomes with a trend toward improved global cognition with minimal adverse events [ 81 - 83 ]. Few other uncontrolled trials, however, have also shown treatment effects with methylphenidate [ 84 , 85 ] and one with donepezil [ 86 ].…”
Section: Management Of Common Neuropsychiatric Syndromes In Alzheimermentioning
confidence: 99%
“…Notwithstanding, there is a rapid increase of prescriptions for ADHD treatment as well as off-label and illicit use [146] of MPH and amphetamines as ''smart pills'' for healthy individuals and as weight loss agents [147,148]. Together with a potential extension of the indication toward ever more potential users-most recently prisoners [149] or Alzheimer patients [30,150]-the percentage of exposed subjects throughout all age classes is bound to increase significantly in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason underlying the increased prescription rate is misuse of stimulants for cognitive enhancement/ neuroenhancement [28][29][30]. MPH is also off-label or illicitly used as a weight loss agent [12].…”
Section: Introductionmentioning
confidence: 99%